(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
contributo sottoposto a valutazione SOMMARIO: 1. L’Eucarestia: “augusto” strumento per la salute deichristifideles nell’economia della salvezza - 2. La transustanziazione - 3. La malattia celiaca e l’unico rimedio terapeutico: la dieta gluten free - 4. Ilchristifidelis affetto dalla sprue celiaca tra dieta gluten free e pane mere triticeus - 5. Prime disposizioni sul divieto dell’uso di ostie quibus glutinum ablatum est - 6. La particola con “una minima quantità di glutine” - 7. Le vigenti prescrizioni sulla validità della materia eucaristica e l’uso di ostie a basso contenuto di glutine - 8. La normativa sulla comunione dei celiaci tra sospetti e apprezzamenti - 9. Ultime precisazioni sull’uso del pane con poca quantità di glutine - 10. Conclusioni. The health of the christifidelis celiac between diet gluten free and invalidity of the hosts quibus glutinum ablatum est. ABSTRACT: The communion of celiac has aroused the attention of the Congregation for the Doctrine of the Faith for the direct connection between gluten, cause of the disease, and bread mere triticeus, precious element of the Eucharist. The complex matter concerns the impelling urgency to allow the christifidelis celiac to follow a super stricte gluten free diet, necessary way to the protection of his mental and physical health, without expelling him from the eucharistic banquet, indispensable instrument of salvation of his own soul. Therefore, in the saving mission of the Church called to the salus animarum of every man, without discriminating exclusions, direct specific norms are emanated to harmonize the dogmatic demands, connected to the Eucharestic, and the therapeutic needs related to mental and physical health of the faithful with the disease. Such norms have faced the validity of the eucharistic matter sealing the invalidity of the hosts quibus glutinum ablatum est, with a meaningful evolution, during the time. It stays, nevertheless, the suspect of an exhaustive solution of the question that induces to wish new interventions.